PRAKTIK EKONOMI PADA MASA KHULAFAUR RASYIDIN - Rafi Prasojo; Dwi Sintia Rahmawanti; Nailis Surooya; Muhammad Taufiq Abadi; Aris Syafi’i (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is describe economic practices during the time of Khulafaur Rasyidin. This research is library research with a qualitative approach. The data sources used come from various literature journal articles that are relevant to the research topic. The data analysis method used is content analysis of literature sources used in the research. Islamic economic practices developed when the Prophet Muhammad SAW moved to Medina. Since the death of Prophet Muhammad SAW, economic practices continued during the time of Khulafaur Rasyidin. After the Prophet died, Muslims appointed Abdullah bin Abu Quhafah al-Tamimi as first caliph. During his leadership, Abu Bakar faced many problems in the life of his country, namely the existence of apostate groups, the emergence of false prophets, and dissidents paying zakat. During Umar bin Khattab's time, leadership changes were carried out through direct appointment. Umar bin Al-Khathab was the most successful caliph in Islamic history, this can be seen from the progress of the country and the welfare of his people, both in terms of economics, politics, social, security, national defense, as well as the development of science and technology. Because of his success, Westerners nicknamed Umar the Saint Paul of Islam.